Belgium's AfricaMuseum has a dark colonial past – it's making slow progress in confronting this history - Bobineau, Julien (The Conversation, 2023)
The restitution of looted objects from former colonies in Africa is an essential component of post-colonial reparation.
Keywords: 2023-07 July; Colonialism; Decolonization